Analysis of The Determinants of Poverty in East Nusa Tenggara Province - Frischa Elvira Jehadut; Surya Dewi Rustariyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
East Nusa Tenggara Province ranks third as the poorest province in Indonesia, making poverty in NTT one of the urgent issues that requires serious attention from the government.This study aims to determine (1) the simultaneous and partial effects of wage levels, education, and unemployment on poverty in the regencies/cities of NTT Province. The data used is secondary time series data from 2019 to 2023 across 22 regencies/cities in NTT Province. The data analysis technique employs panel data regression using the Eviews 12 analysis tool. The results of the study indicate that wages, education, and unemployment simultaneously influence poverty in the regencies/cities of NTT Province during 2019–2023. Wages and education have a negative and significant partial effect, while unemployment has a positive but not significant partial effect on poverty in NTT Province.